Derivational and Inflectional Morphemes on the Thesis Abstracts - Anggun Purnomo Arbi; Sulistyaningsih Sulistyaningsih; Abd. Syakur; Lestariningsih Lestariningsih (Universitas Pahlawan Tuanku Tambusai, 2022)
An analysis of derivational and inflectional morpheme has great values because sometimes, learners face difficulties in understanding those morphemes. Dealing with this problem, this study was aimed to describe the types of derivational and inflectional morphemes. As this study analyzed the written documents, this study was identified as library research. Subjects of this study were five alumni of the master of English education study program of STKIP PGRI Sidoarjo. Documentation and the researcher himself were recognized as the instruments of this study. The data of this study were all words attached by derivational or inflectional morpheme, and all those data were taken from students’ research abstracts. In analyzing the data, the researcher used content analysis. The results showed that the researcher found and discussed two types of derivational morpheme namely derivational prefix (“-un” and “-in”) and derivational suffix (“-ion”, “-al”, “-ance”, “-er”, “-ive”, “-ity”, “-able”, “-ary”, and “-ly”). However, the researcher found and discussed 5 types of inflectional morpheme covering: plural (-s), possessive (-s’ or ‘s), present (-s or -es), past (-ed), and present participle (-ing).